БАЗОВИЙ ВИМІРЮВАЛЬНИЙ МОДУЛЬ ДЛЯ РЕАЛІЗАЦІЇ ВИСОКОТОЧНИХ ЗАСОБІВ ВИЗНАЧЕННЯ ПАРАМЕТРІВ ІМПЕДАНСУ В ШИРОКОМУ ДІАПАЗОНІ ЧАСТОТ - Мельник, В.Г.; Борщов, П.І.; Бєляєв, В.К.; Василенко, О.Д.; Ламеко, О.Л.; Сліцький, О.В. (Інститут електродинаміки Національної академії наук України, 2020)
In the paper fundamentally new technical solutions for the formation of test and reference signals are discussed, as well as for the processing of measuring signals in the impedance measurement channel, which can improve the efficiency of extracting useful information about the state of the measurement object in the wide frequency range. A new method of parallel-serial analog-to-digital conversion of the measuring signal with its modulation and continuous synchronized integration is presented, which allows to increase the amount of information received in a short time, including from moving objects, to increase the suppression of noise and interference from the power network. To increase the accuracy of measurements in a wide frequency range, new structures of impedance parameter meters have been developed, in particular a bridge circuit with balancing over the phase angle and the measuring signal module. The proposed set of technical solutions allowed us to develop and implement experimental samples of the basic module of the measuring channel to determine the impedance parameters with flexible functions, which is competitive in technical and economic characteristics with the best samples of similar equipment from leading world manufacturers . The results of experimental studies of the main characteristics of the created devices are presented. References 6.